Self-efficacy, Innovative Work Behavior and Job Performance in Digital Printing - Chamdan Purnama; Mirhamida Rahmah; Dinda Fatmah (Universitas Muhammadiyah Jakarta, 2022)
Human resources in organizations play a very important role because the company's success in achieving its goals cannot be separated from the role of its employees. Organizational progress will also be achieved if human resources have good performance. The reason for this study was to clarify the effect of direct and indirect self efficacy against job performance through innovative work behavior.This review was planned as explanatory research that intends to give a clarification of the causal connection between variables through theory testing and expects to acquire proper testing in making causal determinations. The example of this review was 96 respondents from the workers of Digital Printing Mojokerto East Java, using a saturated sampling technique.This review utilizes fractional least squares relapse with the Smartpls adaptation 3.0 program. It observes that self-viability straightforwardly has no critical impact on work execution. Be that as it may, self adequacy by implication significantly affects work execution. This shows that creative work conduct can intervene the impact of self adequacy on work execution of organization representatives.